Genomic and Epigenomic Landscapes of Adult De Novo Acute Myeloid Leukemia - Ley, Timothy J; Miller, Christopher; Ding, Li; Raphael, Benjamin J; Mungall, Andrew J; Robertson, A Gordon; Hoadley, Katherine; Triche, Jr, Timothy J; Laird, Peter W; Baty, Jack D; Fulton, Lucinda L; Fulton, Robert; et al. (The New England journal of medicine, 2013)
More than 25% of patients with AML carry no mutations in genes known to be associated with leukemia. Analyses of genomes, transcriptomes, and methylomes of AML samples implicate mutations in cytogenetically normal AML and provide insight into the relationships among causative genes. The molecular pathogenesis of acute myeloid leukemia (AML) has been studied with the use of cytogenetic analysis for more than three decades. Recurrent chromosomal structural variations are well established as diagnostic and prognostic markers, suggesting that acquired genetic abnormalities (i.e., somatic mutations) have an essential role in pathogenesis. 1 , 2 However, nearly 50% of AML samples have a normal karyotype, and many of these genomes lack structural abnormalities, even when assessed with high-density comparative genomic hybridization or single-nucleotide polymorphism (SNP) arrays 3 – 5 (see Glossary). Targeted sequencing has identified recurrent mutations in FLT3, NPM1, KIT, CEBPA, and TET2 . 6 – 8 Massively parallel . . .